Implementasi Kegiatan Ekstrakulikuler Keagamaan dalam Menanamkan Nilai Religius Siswa di MI Ma’arif Depokrejo Kebumen - Adelia Uswatun Hasanah; Faisal Faisal; Nadia Raifa Nawa Kartika (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
Madrasas and teachers are very important in instilling the values of students' religious personality.Madrasas are places that have a great influence on instilling and developing religious values andbehavior both as individual beings and as social beings. The Research Objectives are : 1) To findout how the implementation of religious extracurricular activities in instilling religious values instudents at MI Ma'arif Depokrejo, 2) to find out what are the challenges faced in implementingreligious extracurricular activities at MI Ma'arif Depokrejo. This research is a qualitative research.Data was collected by observation, interviews and documentation. The subjects in this study wereFaridah Wahyuningsig, S.Pd.I, as a religious extracurricular teacher and students taken from classIV. Then analyzed through data reduction, data presentation and conclusions and data verification.Based on the results of the research obtained, it shows that (1) religious extracurricular activitiesat MI Ma'arif Depokrejo run according to Madrasa planning, 2) extracurricular activities ininstilling religious values in students have religious values, namely: faith values, worship values,and moral values.